Physical inactivity rapidly induces insulin resistance and microvascular dysfunction in healthy volunteers - Hamburg, Naomi M; McMackin, Craig J; Huang, Alex L; Shenouda, Sherene M; Widlansky, Michael E; Schulz, Eberhard; Gokce, Noyan; Ruderman, Neil B; Keaney, Jr, John F; Vita, Joseph A (Arteriosclerosis, thrombosis, and vascular biology, 2007)
Sedentary lifestyle increases the risk of cardiovascular disease and diabetes. Vascular dysfunction contributes to atherogenesis and has been linked to insulin resistance. We measured insulin sensitivity by glucose tolerance test and vascular function by ultrasound and venous occlusion plethysmography in 20 healthy subjects (14 men, 6 women) at baseline and during 5 days of bed rest. Bed rest led to a 67% increase in the insulin response to glucose loading (P<0.001) suggesting increased insulin resistance and produced increases in total cholesterol and triglycerides. Bed rest led to decreased reactive hyperemia in the forearm (1317+/-404 to 1112+/-260 mL/min, P=0.01) and the calf (28.5+/-7.0 to 22.2+/-8.7 mL/min/dL, P=0.003) indicating impaired microvascular function. Bed rest decreased brachial artery diameter and increased systolic blood pressure suggesting increased basal arterial tone. There were no changes in circulating inflammatory markers arguing against systemic inflammation as a mechanism for vascular dysfunction in this setting. Physical inactivity was associated with the development of insulin resistance, dyslipidemia, increased blood pressure, and impaired microvascular function in healthy volunteers. Our findings may provide insight into the pathogenesis of vascular disease in sedentary individuals and emphasize that even short-term physical inactivity may have adverse metabolic and vascular consequences.